Herpes zoster case with extremity involvement after chickenpox infection in a healthy infant - Gözde Emel Gökçek; Emine Çölgeçen (Galenos Publishing House, 2021)
Herpes zoster is a dermatomal condition characterized by painful vesiculopapules on an erythematous background, resulting from the reactivation of varicella-zoster virus (VZV) hidden in the dorsal root ganglia. Although it is more common in older and immunosuppressed people, it can be seen at any age. It very rarely occurs in the infantile period, and in healthy infants, herpes zoster usually develops after intrauterine exposure to the virus. Herein, we present the case of a 12-month-old girl who developed a rare form of herpes zoster on the extremities after postnatal VZV exposure.